(untitled) (Journal of Global Arts Studies, 2025)
Background: As a representative intangible cultural heritage project in Changshu area of southern Jiangsu province, Xupu flower drum carries rich regional cultural information with its unique body narrative style, and shows the charm and connotation of folk sports in southern Jiangsu. Objective: Starting from the perspective of intangible heritage, this study deeply discusses the phenomenon of body narrative in folk sports in southern Jiangsu province, aiming to reveal the cultural logic and social value behind Xupu flower drum. Methods: The qualitative research method was adopted to collect data through field investigation, interview and literature analysis, and interpret it from multiple dimensions by using body narrative theory. Results: From physical memories of fishing port life to bodily performances in family rituals, and through the historical evolution from ritual narratives to artistic exhibitions, this demonstrates its profound cultural heritage. In terms of bodily narrative structure, Xupu Flower Drum constructs a unique cultural expression system through three dimensions: symbolic bodies, self-actualizing bodies, and socialized bodies. Conclusion: The protection of Xupu flower drum needs to realize the transformation from "form imitation" to "narrative inheritance", which has important reference value for the creative transformation of folk sports.